PAYMENT SYSTEMS APPLICATIONS COURSE IN ENGLISH COURSE INSTITUTION IEC - Zul Ferizal Hermin; Eko Hadiyanto,SSi, MM (Jurnal Sistem Informasi, 1997)
With this application programs or the work of administrative tasks will be furtherfacilitated. Because the administration can simply enter data about students andcomputers that will manage it, so to minimize the possibility of the things we do notwant, such as loss of data due to scattered and so on, besides it can save time, effortand money.